RH Laksmana's Yam Flour Market Expansion with Technology and Digital Marketing : Ekspansi Pasar Tepung Ubi RH Laksmana dengan Implementasi Teknologi dan Pemasaran Digital - Putri Madona; Zaira, Jupri Yanda; Wijianto, Agus; Henim, Silvana Rasio; Trisnadoli, Anggy; Chandra, Irwan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Cassava is one of the primary food commodities with a strategic role in supporting food security. In Riau Province, cassava production centers continue to grow annually. One of the cassava-based products with increasing demand in both national and international markets is cassava flour. RH Laksmana Cassava Flour is a producer located in Kampar Regency, relying on sunlight for drying cassava chips and manually sieving flour using a 40 cm kitchen sieve, which is inefficient. Marketing efforts are limited to personal social media accounts. This community service project implemented two machines, provided a website and its training, and conducted digital marketing training. Results showed a 41.6% improvement in sieving time efficiency and a 140% increase in sieved production output. Drying processes also became more hygienic and weather-independent, with a capacity of 160 kg/day